(N|KONOMIKA(B, (NORGANIZACIQ I PLANIROWANIE PROMY[LENNOGO PREDPRIQTIQ (B:s (Nu^EBNOE POSOBIE (B/s - (NkAMENICER(B, (NsOLOMON eFREMOWI^s; (NkONTOROWI^(B, (NwENIAMIN gAM[EEWI^s; (NpI]ULIN(B, (Ng(B.s ((NmOSKWA (B:s (NgOSPOLITIZDAT (B,s, 1958)
(NbIBLIOGR(B. (NS(B. 495-499s
Keywords: (NpROMY[LENNYE PREDPRIQTIQ (B- (NoRGANIZACIQ PROIZWODSTWAs; (NpROMY[LENNYE PREDPRIQTIQ (B- (N|KONOMIKAs; (NpROMY[LENNYE PREDPRIQTIQ (B- (NpLANIROWANIEs